Effect of Service and Collaborative Learning Strategies on Learners’ Environmental Attitude - ALALADE, Olufiropo Emmanuel (PT Keberlanjutan Strategis Indonesia, 2023)
Environmental issues have become recurring phenomena at international forums. This empirical paper investigates the effects of service learning and collaborative learning on Junior Secondary School students' environmental attitudes. Learners are exposed to environmental studies through many school subjects, and learning strategies have helped to increase students' knowledge and awareness about environmental issues. However, environmental challenges and problems are still on the increase in Nigeria. The students are also culpable as their attitude does not reflect what they learn. This paper is premised on the cognitive dissonance theory. The quantitative study employed the multistage sampling technique. The results revealed that there was a significant effect of treatment (service and collaborative learning strategies) on junior secondary school students environmental attitude (F(2,582) = 1317.79; p<0.05, partial ?2 = 0.819). Based on this finding, it was recommended that teachers adopt service and collaborative learning strategies in teaching environmental concepts and problems to improve student performance and, more importantly, positively influence their attitudes. Teachers should use service and collaborative learning strategies to provide practical experience for students to be well-grounded and equipped to use these strategies.